METHODOLOGY FOR DEVELOPING STUDENTS’ ACTIVE THINKING AND MENTAL SKILLS IN PRIMARY SCHOOL MOTHER TONGUE LESSONS - Shodmonqulova Dilorom Khalikovna; Yuldasheva Sharapat; Hayitov Anvar Isomidin ugli (The Bioscan, 2025)
This article highlights the content and methods of developing active thinking and mental abilities of students in primary school mother tongue lessons. It focuses on strategies that encourage logical reasoning, creativity, and linguistic competence through interactive learning activities. The study examines pedagogical approaches that stimulate students’ speech development and enhance their ability to express thoughts clearly and effectively. Keywords Primary school, mother tongue, active thinking, development of thinking, speech, speech development, language, speech range.